Chinese Herbal Formula, Modified Danggui Buxue Tang, Attenuates Apoptosis of Hematopoietic Stem Cells in Immune-Mediated Aplastic Anemia Mouse Model - Jingwei Zhou; Xue Li; Peiying Deng; Yi Wei; Juan Liu; Meng Chen; Yamei Xu; Dongmei Zhang; Lingqun Zhu; Lixia Lou; Bin Dong; Qiushuo Jin; et al. (Journal of Immunology Research)
A derivative formula, DGBX, which is composed of three herbs (Radix astragali, Radix Angelicae sinensis, and Coptis chinensis Franch), is derived from a famous Chinese herbal formula, Danggui Buxue Tang (DBT) (Radix astragali and Radix Angelicae sinensis). We aimed to investigate the effects of DGBX on the regulation of the balance between proliferation and apoptosis of hematopoietic stem cells (HSCs) due to the aberrant immune response in a mouse model of aplastic anemia (AA). Cyclosporine (CsA), an immunosuppressor, was used as the positive control. Our results indicated that DGBX could downregulate the production of IFNγ in bone marrow cells by interfering with the binding between SLAM and SAP and the expressions of Fyn and T-bet. This herbal formula can also inhibit the activation of Fas-mediated apoptosis, interferon regulatory factor-1-induced JAK/Stat, and eukaryotic initiation factor 2 signaling pathways and thereby induce proliferation and attenuate apoptosis of HSCs. In conclusion, DGBX can relieve the immune-mediated destruction of HSCs, repair hematopoietic failure, and recover the hematopoietic function of HSCs in hematogenesis. Therefore, DGBX can be used in traditional medicine against AA as a complementary and alternative immunosuppressive therapeutic formula.